An integrated approach towards conservation of traditional patterns in Chinese traditional villages: a systematic literature review - Gao, Lihui; Mohd. Ariffin, Noor Fazamimah; Hussein, Mohd Kher; Liu, Shan; Wang, Beibei (e-IPH Ltd., 2024)
In recent years, the Chinese government and the local government have issued many conservation documents for traditional villages. However, the conservation of traditional patterns has still not been significantly improved. Therefore, this paper explores the conservation approaches of traditional patterns in traditional villages with a systematic literature review. The study suggests that adopting necessary conservation and safeguarding measures, harmonizing conflicts between policies and legislation, improving public participation measures in local communities, and formulating adaptive utilization can promote the conservation and development of traditional patterns of traditional villages.